Angiopoietin-Like Protein 4 is Differentially Regulated by Glucocorticoids and Insulin in vitro and in vivo in Healthy Humans - van Raalte, D. H.; Brands, M.; Serlie, M. J.; Mudde, K.; Stienstra, R.; Sauerwein, H. P.; Kersten, S.; Diamant, M. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Angiopoietin-like protein 4 (Angptl4) is a circulating inhibitor of plasma triglyceride clearance via inhibition of lipoprotein lipase. The aim of the present study was to examine the regulation of Angptl4 by glucocorticoids and insulin in vivo in humans, since these factors regulate Angptl4 expression in vitro.In a randomized, placebo-controlled, double-blind, dose-response intervention study, 32 healthy males (age: 22±3 years; BMI 22.4±1.7 kg m − 2) were allocated to prednisolone 30 mg once daily (n=12), prednisolone 7.5 mg once daily (n=12), or placebo (n=8) for 2 weeks. Angptl4 levels and lipid metabolism were measured before and at 2 weeks of treatment, in the fasted state and during a 2-step hyperinsulinemic clamp. Additionally, human hepatoma cells were treated with dexamethasone and/or insulin.Compared to placebo, prednisolone treatment tended to lower fasting Angptl4 levels (P=0.073), raised fasting insulin levels (P=0.0004) and decreased fasting nonesterified fatty acid concentrations (NEFA) (P=0.017). Insulin infusion reduced Angptl4 levels by 6% (plasma insulin ~200 pmol/l, P=0.006) and 22% (plasma insulin ~600 pmol/l, P<0.0001), which was attenuated by prednisolone treatment (P=0.03). Prednisolone 7.5 mg and 30 mg dose-dependently decreased insulin-mediated suppression of lipolysis (by 11±5% and 34±6% respectively). Prednisolone 30 mg enhanced fasting triglyceride levels (P=0.028). Plasma Angptl4 was not related to prednisolone-induced changes in lipid metabolism. In human hepatoma cells, dexamethasone increased Angptl4 mRNA expression and protein secretion, whereas insulin had the opposite effect.Insulin lowers plasma Angptl4 levels in humans by lowering NEFA and by inhibiting Angptl4 expression and release. Glucocorticoids counteract insulin-mediated suppression of Angptl4.
Keywords: angiopoietin-like protein 4; glucocorticoids; insulin; prednisolone